2019
DOI: 10.3390/rs11202431
|View full text |Cite
|
Sign up to set email alerts
|

Upper Ocean Response to Two Sequential Tropical Cyclones over the Northwestern Pacific Ocean

Abstract: The upper ocean thermodynamic and biological responses to two sequential tropical cyclones (TCs) over the Northwestern Pacific Ocean were investigated using multi-satellite datasets, in situ observations and numerical model outputs. During Kalmaegi and Fung-Wong, three distinct cold patches were observed at sea surface. The locations of these cold patches are highly correlated with relatively shallower depth of the 26 °C isotherm and mixed layer depth (MLD) and lower upper ocean heat content. The enhancement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
(88 reference statements)
0
17
1
Order By: Relevance
“…This finding agrees with the one reported in Avila-Alonso et al (2019) for the waters surrounding Cuba since they found a progressive post-storm surface cooling during a month after the passage of hurricanes, which was partially determined by the passage of consecutive hurricanes across the study area. Moreover, extensive and long-lasting SST cooling as well as intense post-storm phytoplankton blooms after the passage of consecutive TCs have been documented in the northwestern Pacific Ocean (e.g., Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020). Overall, consecutive TCs superimpose effects on the upper ocean response because of strong-induced mixing and upwelling (Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020).…”
Section: Climatological Analysis Of Sea Surface Temperature and Chlormentioning
confidence: 99%
See 2 more Smart Citations
“…This finding agrees with the one reported in Avila-Alonso et al (2019) for the waters surrounding Cuba since they found a progressive post-storm surface cooling during a month after the passage of hurricanes, which was partially determined by the passage of consecutive hurricanes across the study area. Moreover, extensive and long-lasting SST cooling as well as intense post-storm phytoplankton blooms after the passage of consecutive TCs have been documented in the northwestern Pacific Ocean (e.g., Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020). Overall, consecutive TCs superimpose effects on the upper ocean response because of strong-induced mixing and upwelling (Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020).…”
Section: Climatological Analysis Of Sea Surface Temperature and Chlormentioning
confidence: 99%
“…Moreover, extensive and long-lasting SST cooling as well as intense post-storm phytoplankton blooms after the passage of consecutive TCs have been documented in the northwestern Pacific Ocean (e.g., Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020). Overall, consecutive TCs superimpose effects on the upper ocean response because of strong-induced mixing and upwelling (Wu and Li, 2018;Ning et al, 2019;Wang et al, 2020).…”
Section: Climatological Analysis Of Sea Surface Temperature and Chlormentioning
confidence: 99%
See 1 more Smart Citation
“…Distinguishing between mechanisms inducing changes in chl a concentration is crucial to understanding the impact of storms on upper-ocean oceanographic conditions. Although there have been extensive studies investigating the oceanic response described above to the passage of individual TCs, the effects induced by consecutive TCs have been much less documented (Wu and Li, 2018;Ning et al, 2019). More specifically, extensive and long-lasting SST cooling and intense post-storm phytoplankton blooms after the passage of consecutive TCs have been documented in the northwestern Pacific Ocean (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our previous works (e.g., [2,50,[88][89][90][91][92][93]) indicate thatoceanic thermohaline and dynamic features play an important role in upper ocean response to a single or sequential typhoons based on multiple observation data and model simulations. However, these works were mainly in the marginal sea (the South China Sea) and we may further follow the study of this paper, and study how some special topographic features such as with many islands or straits influences the structure of the oceanic response to typhoons in the future.…”
Section: Future Workmentioning
confidence: 96%